The effects of word frequency and typographical enhancement on incidental vocabulary learning in reading. (2nd January 2019) - Sánchez Gutiérrez, Claudia H.; Serrano, Mercedes Pérez; García, Pablo Robles
ABSTRACT: This study examines the effects of word frequency and typographical enhancement (i.e., words in bold) on the learning of single words in Spanish L2 reading activities in a classroom setting. Learners read a text in which target words appearing in bold occurred one, five or 10 times. A parallel text was also provided in which those same words appeared un-bolded. Students were tested three times on both spelling and meaning of the target words: before, immediately after and two weeks after the reading activity. Results show that: (1) after five or 10 encounters, both spelling and meaning recognition skills increase; (2) words appearing in bold only lead to learning gains at a form recognition level immediately after the test is taken and do not contribute to the acquisition of meaning in the post-test; and (3) there is no interaction between typographical enhancement and frequency.